2005
DOI: 10.1577/m04-075.1
|View full text |Cite
|
Sign up to set email alerts
|

Electroshocking and PIT Tagging of Juvenile Atlantic Salmon: Are There Interactive Effects on Growth and Survival?

Abstract: Electroshocking and tagging of fish with passive integrated transponder (PIT) tags are two commonly used methods for conducting mark-recapture studies in freshwater environments and are frequently used in combination. We conducted an experiment to test for the effects of electroshocking, tagging, and a combination of electroshocking plus tagging on the growth and survival of Atlantic salmon Salmo salar parr. We used five treatments that included the presence or absence of PIT tags and electroshocking at 300 or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
38
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 25 publications
12
38
0
Order By: Relevance
“…The majority of mortality (80%) occurred in fish 80 to 84 mm FL. This is in agreement with results from other studies that typically report higher mortalities in smaller individuals following tagging [18,21,24,25]. For example, Acolas et al [21] demonstrated that increases in length of juvenile brown trout (41 to 70 mm FL) significantly enhanced the probability of survival after implantation of 11.5 mm PIT tags.…”
Section: Mortalitysupporting
confidence: 90%
See 3 more Smart Citations
“…The majority of mortality (80%) occurred in fish 80 to 84 mm FL. This is in agreement with results from other studies that typically report higher mortalities in smaller individuals following tagging [18,21,24,25]. For example, Acolas et al [21] demonstrated that increases in length of juvenile brown trout (41 to 70 mm FL) significantly enhanced the probability of survival after implantation of 11.5 mm PIT tags.…”
Section: Mortalitysupporting
confidence: 90%
“…For example, Acolas et al [21] demonstrated that increases in length of juvenile brown trout (41 to 70 mm FL) significantly enhanced the probability of survival after implantation of 11.5 mm PIT tags. Similar results have been reported for Atlantic salmon parr (60 to 69 mm FL) using 11.5 mm PIT tags [24].…”
Section: Mortalitysupporting
confidence: 88%
See 2 more Smart Citations
“…The absence or delay of growth can be explained by stress induced by tagging. In fish studies, while some authors did not report any effect of PIT-tagging on growth (Acolas et al, 2007;Lee et al, 2009;Navarro et al, 2006), others researchers found a reduction in short-term growth (Baras, Westerloppe, Mélard, & Philippart, 1999;Lacroix, Knox, & McCurdy, 2004;Sigourney, Horton, Dubreuil, Varaday & Letcher, 2005). Cucherousset, Paillisson, and Roussel (2007) found that the effect on growth was independent of the size of their studied fish, whereas Greenstreet and Morgan (1989) determined that a minimum size of 160 mm for Atlantic salmon prevented a tag effect on growth.…”
Section: Discussionmentioning
confidence: 99%